Perbandingan Koagulan Komersial dan Biokoagulan Biji Pepaya Pada Flokulasi Hydrocyclone Terbuka Dalam Menurunkan Total Suspended Solid (TSS) - Maulana Rohman Bahari; Aussie Amalia (Faculty of Engineering, Universitas Serambi Mekkah, 2025)
Various methods of clean water treatment have been developed to meet the needs of communities, one of which is coagulation-flocculation, an effective process for removing TSS and turbidity. This process involves mixing coagulants to form flocs, followed by aggregation of suspended particles to facilitate sedimentation. Reactor modifications, such as hydrocyclone flocculators, are designed to improve efficiency, although their effectiveness depends on the size and density of the flocs. Chemical coagulants such as alum and PAC are widely used because of their effectiveness, but their residues can be potentially toxic. As an alternative, biocoagulants such as papaya seeds have been developed to provide a safer solution and produce biodegradable residues. A study was carried out to compare the efficacy of alum, PAC and biocoagulants using a hydrocyclone flocculator with test waters representing low, medium and high TSS levels. Samples were taken at 0, 5, 10, 15 and 20 minutes. The results showed that PAC had the highest efficiency with an average of 78.9% for high TSS, 75% for moderate TSS and 70.8% for low TSS.